Studies on Unsupported Nano-MoS2 Catalyst: A Review - Guo, Fan; Zhu, Yuqin; Li, Rongchun (Asian Journal of Chemistry, 2014)
Unsupported MoS2 hydrodesulfurization (HDS) catalysts shall be concerned for they are sulfided when used without adding toxic sulfur compounds and have ultra-high capacity to hydrodesulfurization. This paper reviewed the progress of the unsupported nano MoS2 catalysts, including the preparation, characterization and desulfurization mechanism.